Olfactory-like neurons are present in the forehead of common cuttlefish, Sepia officinalis Linnaeus, 1758 (Cephalopoda: Sepiidae) - Campinho, Marco António (2018)
According to the literature, the cuttlefish, Sepia officinalis, possesses a specialized olfactory organ and cells, located in olfactory ventral pits. In this study, the location of olfactory receptor neurons (ORNs) at the cellular level was determined using cellular morphology and immunohistochemistry. An antiserum against PBP3 was used as a marker to identify ORN-like cells in cuttlefish after validation for specificity to cephalopod ORN cells in the common octopus, Octopus vulgaris. The results show that ORN-like cells in S. officinalis were not found in the ventral pits, suckers or the mouth lips. Instead, ORN-like cells were found scattered in the forehead, between the eyes. The absence of ORNlike cells in a pit in S. officinalis and the sharing of four similar types of ORN cells with the squid and octopus lineages suggest that this might be a later innovation in olfaction and is probably associated with the specialized lifestyle of these later evolved cephalopods. Together, this evidence suggests a diversification of ORN cell types in Coleoidea, which did not occur in Nautiloidea, which might have preceded the diversification of the Coleoidea.